Investigation of the Influence of Tool Geometry on Effective Strain Distribution in Full Forward Extrusion - Merklein, Marion; Ndzomssi, Franck; Engel, Ulf (AIP Conference Proceedings, 2011)
Due to strain hardening of the material, the hardness of cold forged parts is considerably improved. It is well known that the hardness of cold forged parts is closely related to its deformation, and that this relation is not dependent on the deformation process. The effective strain defines the local deformation, and can be determined in simulation of the cold forming process. In order to reach the required or to set specific hardness distribution with cold forging without any heat treatment processes, it is necessary to find out which manufacturing parameters influence the effective strain, and determine the effects of these parameters. The research work covered in this paper investigates the influence of the die geometry (as manufacturing parameter) on the effective strain. For that, a full forward extrusion process was modeled using the FE-software Simufact. Forming and three parameters of the die geometry, namely the deformation ratio, the shoulder radius and the opening angle were varied. The maximum effective strain from each combination is determined, and the effects of each considered parameter as well as the effects of interactions between these factors are checked. © 2011 American Institute of Physics.
LFT Import::2019-07-29 (1692)
Keywords: deformation ratio; Design of Experiments; effective strain; Finite Elements Method; full forward extrusion